2021
DOI: 10.1007/s10668-021-01649-w
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of sustainability (ESG) disclosure on firm value and financial performance (FP) in airline industry: the moderating role of size and age

Abstract: This study aims at exploring the impact of ESG scores on the value and FP of firms in the airline industry. The potential moderating role of firm size and age has also been studied in an effort to disentangle their relationships in this context. In particular, the analysis involves interaction effects for two types of firms: full-service and low-cost carriers. Based on the collected data from 38 airlines worldwide for the period 2009 to 2019, we observed that contributions to governance initiatives improve a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(134 citation statements)
references
References 83 publications
4
74
0
1
Order By: Relevance
“…There are other external factors with high influence, such as the Indian national system, which is considered to be influential in the desired, future-state state. Regarding the importance assigned to the relation with the stakeholders, in terms of aeronautical customers, some authors have reported that an airliner's participation in social and environmental activities is positively and significantly correlated with a higher level of financial efficiency [43]. In order to avoid environmental degradation, stakeholders increasingly require green-friendly practices and disclosure [44].…”
Section: Tasl Resultsmentioning
confidence: 99%
“…There are other external factors with high influence, such as the Indian national system, which is considered to be influential in the desired, future-state state. Regarding the importance assigned to the relation with the stakeholders, in terms of aeronautical customers, some authors have reported that an airliner's participation in social and environmental activities is positively and significantly correlated with a higher level of financial efficiency [43]. In order to avoid environmental degradation, stakeholders increasingly require green-friendly practices and disclosure [44].…”
Section: Tasl Resultsmentioning
confidence: 99%
“…In another study (Abdi, et al 2022) based on the collected data from 38 airlines worldwide for the period 2009 to 2019, it was revealed that contributions to governance initiatives improve a civil aviation firm's market-to-book ratio. It was also found that a firm's participation in social and environmental activities is positively and significantly rewarded by a higher level of financial efficiency in the airline industry.…”
Section: Studies On Ancillary and Cargo Revenues In Aviationmentioning
confidence: 99%
“…Several studies support the positive correlation between the implementation of environmental, social, and governance (ESG) reporting and the firm value and financial performance of airlines. Abdi et al (2022) demonstrated that, while ESG activities may reduce airlines' short-term financial performance, they can have a significant positive impact on their overall financial performance. Kuo et al (2021) reached the same conclusion by analyzing 30 airline companies worldwide for five years.…”
Section: Improved Firm Value and Financial Performancementioning
confidence: 99%